Tumor desmóide intraperitoneal - Furtado, José Pio (2023)
The authors, in relation to a case of intra-peritoneal desmoid tumor, present the pathological and therapeutical aspects of this intriguing neoplasia classifiedas a fibromatosis group. The neoplasia was a laparotomy inner surgical finding of a large abdominal mass. It resulted in the complete extraction ofa homogeneousiy massive and nacreous tumor, only adhered to the circumjacent víscera. In the formulation of the differential diagnostic, the authors suggest that the fortuitons occurrence of this neoplasia should be taken into account, mainly in clinical familiar situations.